Knowledge, Attitudes and Practices Regarding Diabetic Neuropathy Among Type-II Diabetics in Jabra Locality, Khartoum, Sudan, in 2022 - Elsiraj, Saeed Eltahir Saeed (International Journal of Medical Students, 2023)
Background Diabetic peripheral neuropathy is a characteristic neurodegenerative disorder of the peripheral nervous system that targets sensory & autonomic axons and later, to a lesser extent, motor axons. Among the complications of diabetes, diabetic peripheral neuropathy is by far the most prevalent. This study aimed to assess the level of knowledge, attitude and practices regarding diabetic neuropathy among Type-II diabetics attending Zenam Specialist Hospital in 2022. Methods This study was conducted as a cross-sectional study in Zenam Specialist Hospital. A previously published validated questionnaire about knowledge, attitudes, and practices (KAP) toward diabetic neuropathy was used in this study with very minor modification to be suitable for Sudanese population. Convenient random sampling was used to collect data. Results Out of 162 participant, 82 (50.6%) were males and 80 (49.4%) of them were females. The age of respondents ranged from 18 to 80 years with mean age of 50.89 ± 12.74 SD. The study indicated that patients with older age had better knowledge (P ≤ 0.017) with Pearson’s correlation coefficient (r) of 0.187. No significant gender difference was noted regarding knowledge score. Patients educated above secondary level (P≤ 0.046) and employed in the government and private sector (P = 0.024) had better knowledge compared to their respective groups. Married participants (P = 0.016) had better knowledge scores compared to others. The maximum knowledge score was 39 / 41. The mean score was 26.71 (95% CI 25.54 – 27.88) and standard deviation (SD) was ± 7.52, with a range of 8 to 39. Maximum attitude score was 8.0. The median score was 7.0 and standard deviation (SD was± 0.83. The maximum practice score was 15/15 The mean score was 10.79 (95% CI for mean 10.32 to 11.26) and standard deviation (SD) was ± 3. Conclusion The study indicated good knowledge about diabetic neuropathy among diabetic patients, moreover, the attitude of participants were also positive. Yet, these two did not necessarily solely affect their practices. This could be attributed to other factors that need further studies.